2020
DOI: 10.1002/ps.6127
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insecticide resistance and molecular mechanisms involved in the West Nile vector Culex pipiens in Morocco

Abstract: BACKGROUND Mosquitoes of the Culex pipiens complex are the vectors of several arboviruses and are thus subjected to insecticide control worldwide. However, overuse of insecticides selects for resistance. While assessing the resistance status of the vectors is required for effective and sustainable disease control, resistance has so far only been sparsely studied in Morocco. In this study, we establish a first countrywide assessment of the levels of resistance to various insecticides and the potential responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…For all AChE mutations, studied populations showed tendencies towards an excess of heterozygotes. Similar results were obtained by some authors (Taskin et al, 2016;Arich et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For all AChE mutations, studied populations showed tendencies towards an excess of heterozygotes. Similar results were obtained by some authors (Taskin et al, 2016;Arich et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…pipiens populations (Alout et al, 2007b;Alout et al, 2009). Although G119S mutation were described around the world, F290V was rarely recorded in Mediterranean countries such as Greece, Morocco, Tunisia, and Türkiye (Alout et al, 2007b;Kioulous et al, 2014;Ben Cheikh et al, 2009;Taskin et al, 2016;Arich et al, 2021). Two different codon combinations were identified at the F290 mutation point causing organophosphate/carbamate resistance in this study, and these combinations were TTT codon (wild type) and GTT codon (encoding valine).…”
Section: Discussionmentioning
confidence: 50%
“…Morocco presents a most suitable opportunity to address this question: similar to the situation in Tunisia and Algeria, a previous analysis showed that both alleles of the CQ11 marker segregate in natural populations, with many heterozygotes [34]. In the present study, we took advantage of this situation to assess the association between autogeny, revealed through ovarian dissection, and CQ11 genotypes.…”
mentioning
confidence: 81%
“…As in previous studies [34,44,45], the genotype at the CQ11 locus was used to understand the character of Moroccan populations (e.g. pipiens-like, molestus-like, intermediate or harboring both discrete types).…”
Section: Cq11 Allele Frequencies Are Similar Across Morocco and Acros...mentioning
confidence: 99%
“…In Morocco, Arich et al found that Cx. pipiens forms pipiens and molestus were resistant to most common insecticide families used in mosquito control as well as in agriculture or urban residuals, all over Morocco [ 197 ]. Further studies are needed to elucidate the reality of insecticide resistance of mosquito vector species in North Africa, in order to promote integrated control strategies.…”
Section: Mosquito Control Strategies In North Africamentioning
confidence: 99%